Sex differences and indications of metabolic compensation in within-day energy balance in elite Division 1 swimmers - Lundstrom, E. A.; De Souza, M. J.; Canil, H. N.; Williams, N. I. (Applied Physiology, Nutrition, and Metabolism, 2023)
To determine whether mismatched energy intake and expenditure across the day and associated sex differences may be related with metabolic compensation and/or negative health outcomes, we assessed total-day and hourly energy balance (TDEB and EB), total-day and hourly energy intake (TDEI and EI), total-day and hourly energy expenditure (TDEE and EE) and within-day energy balance (WDEB) in elite male and female swimmers (n = 25; 18-22 years). Total triiodothyronine (TT3), resting metabolic rate (RMR), and the ratio of actual-to-predicted RMR were determined. Males exhibited higher TDEB (+758 ± 702 kcal vs +52 ± 505 kcal, t-test; p = 0.007) than females. Males exhibited a more positive hourly EB, driven by greater hourly EI at 11:00, 13:00, 16:00, and 19:00 h (ANOVA, p < 0.05), while EE did not differ. TT3 was negatively correlated with consecutive hours of negative EB (R = -0.604, p = 0.049) and positively correlated to hours in EB (R = 0.740, p = 0.009) in those exhibiting metabolic suppression (n = 12). In individuals in TDEB (n = 21), "backloaders" (consumption of =50% daily kcals at or after 1700 h) had lower TT3 (79.3 ng/dL vs 92.9 ng/dL, p = 0.009) than "nonbackloaders" (n = 12). WDEB analyses indicate a greater risk of energy deficiency in females and may capture indices of metabolic compensation not evident with EB analyses alone.